The interaction of COMT genotype, tolcapone and acute stress, on brain activity and working memory performance - Martens, M (2019)
An inverted-U-shaped relationship exists between dopamine and prefrontal cortex (PFC) dependent cognitive function, whereby either too little or too much dopamine signalling impairs cognitive performance. Genetic, pharmacological, pathological, and environmental factors can affect a person’s position on the curve. In this thesis I explored three of such factors and their potential interactions. Interestingly, an inverted-U relationship also exists between acute stress and PFC-dependent cognitive performance, with moderate stress levels facilitating, and high levels impairing cognitive function. The enzyme catechol-O-methyltransferase (COMT) metabolises dopamine in the PFC. The human COMT gene contains a functional polymorphism (Val158Met) that influences enzyme activity: the ancestral COMT-Val allele has ~40% greater activity than the COMT-Met allele. COMT activity can also be altered pharmacologically by inhibitors, like tolcapone. Previous research showed that COMT Val158Met affects the functional connectivity of the PFC at rest and linked the COMT-Met allele with better PFC-dependent performance. Moreover, COMT genotype and tolcapone interact, with the drug having opposite effects on cognition in COMT-Met and COMT-Val homozygotes. The goal of this DPhil project is to extend these findings. In particular, there is evidence that stress also impacts dopamine signalling, and some indication that it interacts with COMT. However, it is unknown whether this interaction is modulated by COMT inhibition by tolcapone. First, two stressors were explored, - a novel VR stressor and the Montreal Imaging Stress Task (MIST). Both induced a physiological and psychological stress response, however with a different magnitude and duration. The MIST induced a stronger and longer lasting physiological response, whilst the VR lift seemed to induce higher subjective ratings of stress and anxiety. The main study of this thesis was a randomised, double-blind, placebo-controlled, between-subjects study of the effects of COMT genotype and tolcapone and their interaction, on behaviour and patterns of brain activity using MRI. I demonstrate that COMT and tolcapone influence cerebral blood flow, resting state functional connectivity, stress sensitivity and working memory related brain activation and performance. However, the majority of my findings are not compatible with a ‘simple’ inverted-U model, whereby stress acts only to increase central dopamine levels and thereby enhance (baseline) performance in COMT-Val homozygotes, and impair it in COMT-Met homozygotes. In future it would be of interest to further study these inverted-Us by investigating how different forms of PFC dependent cognitive functions are affected by different kinds of stressors. However, these relationships are complicated by the fact that some of the cognitive effects of stress are likely mediated by non-dopaminergic mechanisms, the context dependency of the different inverted-U relationships, the stress response not being a unitary concept, and the need for multidisciplinary approaches and falsifiable hypotheses.